Behavioral Biases in Macroeconomics and Macroeconomic Decision-Making - Panse, Clara (2024)
This thesis explores the influence of behavioral biases on macroeconomics and macroeconomic decision-making processes. It examines the impact of various biases on the way economic conditions are judged, policies are created, and market participants behave, distorting macroeconomic results. First, the theoretical foundations are explained, and the methodological approach is laid out. Following this, an overview of the most essential biases that impact macroeconomics and macroeconomic decision-making is given. Next, biases are applied to macroeconomics, covering the fields of forecasting, policy decision-making, and macroeconomic dynamics and markets. Lastly, debiasing and its potential implications for macroeconomics are covered. It concludes by highlighting avenues for future research.